1999
DOI: 10.1046/j.1365-8711.1999.02968.x
|View full text |Cite
|
Sign up to set email alerts
|

Density profiles of dark matter haloes: diversity and dependence on environment

Abstract: We study the outer density profiles of dark matter haloes predicted by a generalized secondary infall model and observed in a dissipationless cosmological simulation of a low‐density flat cold dark matter model with the cosmological constant. We find substantial systematic variations in shapes and concentrations of the halo profiles as well as a strong correlation of the profiles with the environment in which the haloes are embedded. In the N‐body simulation, the average outer slope of the density profiles, β(… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
98
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 57 publications
15
98
1
Order By: Relevance
“…Reported in columns (6) to (14) are, respectively, the virial mass, M v , the maximum circular velocity, V max , the c 1/5 and NFW concentration parameters, the average density within 1% the virial radius, and three core radii estimated by different criteria (the latter quantities apply only to halos simulated with v rms ; see x 4.2). The NFW and c 1/5 concentrations are defined, respectively, as the ratios between R v and the NFW scale radius and those between R v and the radius where one-fifth of M v is contained (Avila-Reese et al 1999). As found in previous results, halos with masses below the truncation mass in the power spectrum tend to be less concentrated than ÃCDM halos of similar masses (Avila-Reese et al 2001; Bode et al 2001;Knebe et al 2002).…”
Section: The Structure Of Halos At the Scale Of Dampingmentioning
confidence: 85%
“…Reported in columns (6) to (14) are, respectively, the virial mass, M v , the maximum circular velocity, V max , the c 1/5 and NFW concentration parameters, the average density within 1% the virial radius, and three core radii estimated by different criteria (the latter quantities apply only to halos simulated with v rms ; see x 4.2). The NFW and c 1/5 concentrations are defined, respectively, as the ratios between R v and the NFW scale radius and those between R v and the radius where one-fifth of M v is contained (Avila-Reese et al 1999). As found in previous results, halos with masses below the truncation mass in the power spectrum tend to be less concentrated than ÃCDM halos of similar masses (Avila-Reese et al 2001; Bode et al 2001;Knebe et al 2002).…”
Section: The Structure Of Halos At the Scale Of Dampingmentioning
confidence: 85%
“…Bullock et al (2001) found that halos in dense environments are more truncated than their isolated counterparts of the same virial mass. Avila-Reese et al (1999, 2005 found that halos in cluster regions are more concentrated than isolated halos. N-body simulations of cluster formation and evolution (Ghigna et al 1998;Ghigna et al 2000) find that the dominant interactions are between the global cluster tidal field and individual galaxies after z = 2.…”
Section: Discussionmentioning
confidence: 99%
“…In their simulations on formation of dark halos, Avila-Reese et al (1999) find that most halos tend to have density profiles ∝r −β where β falls in the range 2.5-3.8, in the outer region. Bournaud et al (2003) find from their simulations, that dark halos should extend to at least ten times further than their stellar disks, ) as a function of the galactocentric radius, for the best-fit halo (p = 2) and the isothermal halo (p = 1).…”
Section: Comparison With Other Deductionsmentioning
confidence: 99%